Responsiveness of Physical Rehabilitation Centers in Capital of Iran: Disparities and Related Determinants in Public and Private Sectors - Alavi, Manijeh; Khodaie Ardakani, Mohammad Reza; Moradi-Lakeh, Maziar; Sajjadi, Homeira; Shati, Mohsen; Noroozi, Mehdi; Forouzan, Ameneh Setareh (Frontiers in Public Health, 2018)
Background: Responsiveness as a non-medical, non-financial goal of the health system is of special importance to people with physical disability. The current study assessed the experiences of people with physical disabilities when they encounter rehabilitation centers in Tehran. Methods: This cross-sectional study was conducted in Tehran, the capital of Iran. The sample consisted of 610 people with physical disabilities referred to 10 comprehensive rehabilitation centers (CRCs) selected by Quota sampling. Data were collected by a standard responsiveness questionnaire proposed by the World Health Organization (WHO) and were analyzed by a standard protocol. Blinder-Oaxaca analysis was done to explain the inequality in performance of public and private sectors. Results: Study participants included 298 (48.7%) women and 312 (51.3%) men. The mean age of the respondents was 46.3 (SD = 14.3) for women and 45.6 (SD = 15.4) for men. Prompt attention (33.3%) and confidentiality (1.3%) were the most and least important reported domains, respectively. Overall poor responsiveness was reported by 20.9% of respondents. Private rehabilitation centers showed significantly better performance in communication, basic amenities and autonomy compared to public centers (P ≤ 0.05). Perceived social class explained 76% of the inequality in autonomy in the private and public sector (P ≤ 0.05). Conclusion: Improving overall responsiveness in domains that are of high importance from the respondents' viewpoint but are performing poorly—areas such as prompt attention and basic amenities—is essential. Additionally, interventions are needed to improve the performance of the public centers and providers in the areas of participation of service users in all social classes in their rehabilitation decisions and procedures, clear communication, and basic amenities.